Mapping Business Process Modeling with the Business Models of Several Energy Community Members - Anca Ioana ANDREESCU; Simona-Vasilica OPREA; Adela BARA; Alin Gabriel VADUVA; Andreea-Mihaela NICULAE (Database Systems Journal, 2024)
Energy communities (ECs) enable decentralized production and distribution of renewable energy. Using Business Process Model and Notation (BPMN), this article maps workflows of key EC actors—prosumers, storage owners, EV-charging facilities, aggregators, and market entities. The resulting process models uncover optimization points for energy use, grid stability, and economic value, demonstrating BPMN’s role in building efficient and resilient decentralized energy systems.